Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

“Come One, Come All”: Blackface Minstrelsy as a Canadian Tradition and Early Form of Popular Culture - Thompson, Cheryl (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues–a group of established and up-and-coming artists, scholars, and cultural critics–argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History–an African Canadian Art History